PREVENTIVE SERVICE DAN PREVENTIVE HEALTH EDUCATION BERDASARKAN TANNAHILL’S MODEL MENINGKATKAN PERILAKU IBU DALAM PENCEGAHAN DIFTERI PADA ANAK DI WILAYAH KERJA PUSKESMAS GADING SURABAYA - Siti Afifaturochmah; Nuzul Qur'aniati; Kristiawati Kristiawati (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Diphtheria is a contagious infectious disease that can be prevented by immunization. But, increase in immunization coverage is not in line with the decline in the incidence of diphtheria in Surabaya. So, health promotion at the preventive level for increase behavior is needed. The purpose of this study is to explain the effect of the implementation of preventive service and preventive health education based on Tannahill's model of mother’s knowledge, attitude and practice in preventing diphtheria.Methods: Design research is the study researchers used a preexperiment with one group pre post test design. In this study, researchers used a purpossivesampling technique performed on 37 mothers who possess of children aged 1-3 years in Kelurahan Gading. Independent variable is preventive services and preventive health education and the dependent variable is the knowledge, attitude and action. Data was collect by questionnaires and observation sheets. Data were analyzed with the Wilcoxon signed rank test statistic test α 0.05.Result: Based on the results of this study showed that program of preventive services and preventive health education based on Tannahill's model affect knowledge significantly (α=0.000), but it also contained a significant improvement on the attitude of the mother (α=0.000), and the act of the mother on the prevention of diphtheria also increased significantly (α=0.000). Discussion: Tannahill model of health promotion form preventive service and preventive health education affect improvement mother’s behaviour in the prevention of diphtheria can be used as an alternative to the model.